Motivation of personnel on machine-building enterprise - Pererva, P. G.; Gutsan, Oleksandr; Diachenko, T. A. (Miskolci Egyetem Gazdaságtudományi Kar, 2017)
The article is devoted to the study of theoretical and methodical aspects of motivation of the personnel of industrial enterprises. Based on the study of existing scientific research, it is specified: the flow of the motivational process, the concept of «competence», the classification of competences in the motivational aspect. In the work, five levels of formation and study of motivation are identified, which systematize the accumulated theoretical and practical experience. A methodical approach is proposed for the formation of groups of motivation factors based on the use of the block-modular method. Methodical support of the mechanism for identifying the key factors of motivation, which allows to identify the factors that have the greatest impact on the employee, has been developed. A methodical approach to the evaluation of motivation factors based on a qualitative and quantitative assessment of the level of motivation is proposed, which makes it possible to carry out an assessment depending on the goals set.
Keywords: staff; principles; functions; factors